2020
DOI: 10.34118/jbms.v7i1.744
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of self- compacting concrete incorporating calcined pyrophyllite as supplementary cementitious material

Abstract: The current trend of industrial concrete leans more towards the use of self-compacting concrete. These must have fresh properties well defined as fluidity, filling ability and resistance to segregation. However, to ensure the rheological stability, use mineral fines is required. In this work, powder of calcined pyrophyllite (CP) was used as cement substitution at level of 10% and 20% by weight. The interest is focused on the role played by the calcined pyrophyllite to produce SCC with reduced impact environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…10%BC, 13%KT1 and 10% MP from 26 cm to 10 cm for binary mixes 50% GC, 50% BC, 70% KT1 and 10% MP. The observed decrease in slump flow is mainly due to the high water demand of calcined clays compared to cement (21,22). It is also reported that, with same w/c ratio, the decrease of fresh SCMo fluidity with the increase of CC may be due to their high specific surface area and irregular grains morphology (23).…”
Section: Wynikimentioning
confidence: 79%
“…10%BC, 13%KT1 and 10% MP from 26 cm to 10 cm for binary mixes 50% GC, 50% BC, 70% KT1 and 10% MP. The observed decrease in slump flow is mainly due to the high water demand of calcined clays compared to cement (21,22). It is also reported that, with same w/c ratio, the decrease of fresh SCMo fluidity with the increase of CC may be due to their high specific surface area and irregular grains morphology (23).…”
Section: Wynikimentioning
confidence: 79%
“…Calcined pyrophyllite has been studied as a cement replacement and it was shown to increase the compressive, tensile, and flexural strength of self-compacted concretes (Mansour 2020).…”
Section: Clarifying Earth Terminologymentioning
confidence: 99%
“…When the perlite is used as cement substitution, PP10, PP15, and PP20 are homogeneous but less stable than PN0. This is due to the increase of the amount of perlite fines in SCC which facilitates the passage through the sieve and increases the milt weight [38].…”
Section: Fresh Properties Of Sccmentioning
confidence: 99%